2021
DOI: 10.5603/gp.a2021.0186
|View full text |Cite
|
Sign up to set email alerts
|

Epidural anaesthesia and myomectomy-associated blood loss: — a prospective randomised controlled study

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Ginekologia Polska" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…There are also few recently published studies on this topic. In 2019, a study revealed that the use of epidural analgesia during twin pregnancies can extend the second stage of labor for both twins, while in 2021, another study examined the impact of epidural analgesia on the delivery mode for the second twin and demonstrated a lower risk of cesarean section [6] , [7] However, in our study the exact reason for the increased proportion of epidural analgesia in twin pregnancies remains unknown due to the register-based study design. Confounding factors, such as higher maternal age and body mass index, gestational diabetes, and a higher proportion of instrumental vaginal deliveries (possibly requiring more pain relief in advance) among women with twin pregnancies might partly explain the higher proportion [13] , but the aORs still showed markedly increased odds for epidural analgesia among women with twin pregnancies.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…There are also few recently published studies on this topic. In 2019, a study revealed that the use of epidural analgesia during twin pregnancies can extend the second stage of labor for both twins, while in 2021, another study examined the impact of epidural analgesia on the delivery mode for the second twin and demonstrated a lower risk of cesarean section [6] , [7] However, in our study the exact reason for the increased proportion of epidural analgesia in twin pregnancies remains unknown due to the register-based study design. Confounding factors, such as higher maternal age and body mass index, gestational diabetes, and a higher proportion of instrumental vaginal deliveries (possibly requiring more pain relief in advance) among women with twin pregnancies might partly explain the higher proportion [13] , but the aORs still showed markedly increased odds for epidural analgesia among women with twin pregnancies.…”
Section: Discussionmentioning
confidence: 77%
“…However, a study published in 2019 found that epidural analgesia in twin pregnancies prolongs the second stage of labor in both twins [6] . In 2021, a study assessed the effects of epidural analgesia on the mode of delivery for the second twin and found that the risk for CS was reduced [7] . However, despite these findings, there are currently no reports on the use of different labor analgesia in twin pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Farghali et al recently performed a prospective analysis of 343 parturients with twin gestation planned for a trial of vaginal delivery to determine the influence of EA on the delivery of the second twin [ 45 ]. The studied parturients received EA, while the control group consisted of parturients who received remifentanil-PCA on account of their ineligibility for EA.…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from the previous study by Chadha et al [ 39 ], a sample size of 103 breech deliveries (37 with EA and 67 controls) would be sufficient to reach a statistical power of 0.8 with an α level of 0.05 when analyzing intrapartum CS rates. For twins, a sample of 10 births with EA and 50 with remifentanil-PCA would be sufficient to reach the same statistical power for intrapartum CS analysis based on data from Farghali et al [ 45 ]. Groups with remifentanil-PCA vs. EA were compared using the Chi-square test.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to also take into account about the myomectomy related blood loss and the anaesthesia provided. Farghali et al [4] studied epidural anaesthesia vs the myomectomy related blood loss and found that in patients whom general anaesthesia was provided there was more blood loss compared to whom epidural was administered. Hence this was an added advantage for us in already anemic patient.…”
Section: Discussionmentioning
confidence: 99%